Immune-mediated hematological disease in dogs is associated with alterations of the fecal microbiota: a pilot study. - Liu, P.-Y.; Xia, D.; McGonigle, K.; Carroll, A. B; Chiango, J.; Scavello, H.; Martins, R.; Mehta, S.; Krespan, E.; Lunde, E.; LeVine, D.; Fellman, C. L; Goggs, R.; Beiting, D. P; Garden, O. A (Tufts University. Tisch Library., 2023)
Keywords: Hemolytic anemia, Thrombocytopenia, Biomarker, Treponema, Clostridium septicum, Escherichia coli, Immune-mediated disease, Dog, Microbiome.; Springer Open.